2018
DOI: 10.1631/jzus.b1700283
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid protein from porcine epidemic diarrhea virus isolates can antagonize interferon-λ production by blocking the nuclear factor-κB nuclear translocation

Abstract: Porcine epidemic diarrhea virus (PEDV) is a highly infectious pathogen that can cause severe diseases in pigs and result in enormous economic losses in the worldwide swine industry. Previous studies revealed that PEDV exhibits an obvious capacity for modulating interferon (IFN) signaling or expression. The newly discovered type III IFN, which plays a crucial role in antiviral immunity, has strong antiviral activity against PEDV proliferation in IPEC-J2 cells. In this study, we aimed to investigate the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Further experiments confirm that N directly interacts with TBK1 to obstruct the association between TBK1 and IRF3, which inhibits TBK1-induced IRF3 phosphorylation and IFN-β production [58]. Moreover, the effect of PEDV N protein on type III IFN production has also been evaluated [168]. N protein inhibits polyinosinic-polycytidylic acid (poly(I:C))-induced IFN-λ3 production by blocking the nuclear translocation of NF-κB, but does not antagonize the type I or type II IFN expression induced by poly(I:C) in IPEC-J2 cells [168].…”
Section: Pedv N Proteinmentioning
confidence: 88%
See 2 more Smart Citations
“…Further experiments confirm that N directly interacts with TBK1 to obstruct the association between TBK1 and IRF3, which inhibits TBK1-induced IRF3 phosphorylation and IFN-β production [58]. Moreover, the effect of PEDV N protein on type III IFN production has also been evaluated [168]. N protein inhibits polyinosinic-polycytidylic acid (poly(I:C))-induced IFN-λ3 production by blocking the nuclear translocation of NF-κB, but does not antagonize the type I or type II IFN expression induced by poly(I:C) in IPEC-J2 cells [168].…”
Section: Pedv N Proteinmentioning
confidence: 88%
“…The evasive strategies utilized by PEDV are classified into four major types: 1) inhibition of RLRs-mediated IFN production pathways, 2)inhibition of the activation of transcription factors responsible for IFN induction, 3) disruption of the signal cascades induced by IFN, and 4) hiding its viral RNA to avoid the exposure of viral RNA to immune sensors. In the past decade, accumulating evidence demonstrates that PEDV N protein, nsp1, PLP2, nsp5, nsp15, and nsp16 antagonize type I IFN or type III IFNs production [58,65,78,80,100,132,135,168]. This explains why only weak IFNs' and cytokines' expression is detected in PEDV-infected cells [169,170].…”
Section: Immune Evasion Mechanisms Of Pedvmentioning
confidence: 99%
See 1 more Smart Citation
“…N protein also plays an important role in viral pathogenesis Likai et al, 2019;Shi et al, 2017;Zhang et al, 2015Zhang et al, , 2014. PEDV N protein can antagonize beta interferon and interferon-λ production (Ding et al, 2014;Shan et al, 2018). SARS-CoV N protein can bind to DNA in vitro (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Genome comparisons between the prototype strain CV777 and PEDV variants showed that the differences were mainly concentrated in the S1 subunit which is important for studying the genetic relationships among different PEDV strains and for epidemiological investigations .The N protein is a highly conserved phosphoprotein, only a few point mutations have been reported to date. It has multiple functions in viral replication, assembly, and pathogenesis, for example, it can block nuclear factor-κB nuclear translocation, antagonizing interferon-λ production (Shan et al, 2018) and may also be a promising target for vaccine development research due to its antigenicity.…”
Section: Introductionmentioning
confidence: 99%